2017
DOI: 10.46743/2160-3715/2017.2551
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning in Action: A Collaborative Inquiry

Abstract: In this paper, we describe a case study of an undergraduate course on research methodology, in which lecture was reduced to a minimum and replaced with experiential learning activities. The course design was project-based and spiraled through four phases: a mini-lecture on a given research method, an “early practice” activity, and “reflection on practice” tutor-guided small group collaborations which led to deeper understanding of the given research method. This particular course design constitutes a paradigm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The original form of interaction in the mathematics class described above revealed that students were expected to "learn mathematics" and not to "do mathematics," adopting a passive role with minimal involvement in the emerging class dialogue. In the context of the (re)shaping process of the inquiry class, the form of the interaction changed from teacher-centered to student-centered, facilitating interaction among students (Brailas et al, 2017), and "planning time for children to pose and to solve their own problems, and watching and listening but intervening only to inspire children's mathematical investigations" (Cheeseman, 2019, p. 11).…”
Section: Discussionmentioning
confidence: 99%
“…The original form of interaction in the mathematics class described above revealed that students were expected to "learn mathematics" and not to "do mathematics," adopting a passive role with minimal involvement in the emerging class dialogue. In the context of the (re)shaping process of the inquiry class, the form of the interaction changed from teacher-centered to student-centered, facilitating interaction among students (Brailas et al, 2017), and "planning time for children to pose and to solve their own problems, and watching and listening but intervening only to inspire children's mathematical investigations" (Cheeseman, 2019, p. 11).…”
Section: Discussionmentioning
confidence: 99%
“…By sharing stories and empowering narratives, we can establish a more democratic classroom culture; a transformative community practice that promotes the development of autonomous human beings (Brailas, Avani, et al, 2017). An autonomy attained through and for interdependence (Vassiliou & Vassiliou, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The emphasis has been mainly on the side of the participants' safety, and the researchers' side is usually overlooked: "We were surprised to uncover a gap in the literature pertaining to the emotional wellbeing of doctoral students researching with vulnerable populations" (Velardo & Elliott, 2018, p. 212). When the peer group prioritizes an appreciative culture, members have the opportunity to express themselves authentically and articulate their unspoken thoughts, without the fear of being criticized or disrespected (Brailas, Avani, et al, 2017;Brailas et al, 2019). By doing so, they gradually come to understand that their own feelings of incompetence are neither uncommon nor something to be demonized or hidden, but, instead, something they should acknowledge and take advantage of in their practice (Holloway & Johnston, 1985).…”
Section: Form and Participate In Peer Supervision Groupsmentioning
confidence: 99%